2023
DOI: 10.3390/foods12152928
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Comparison of the Digestibility and Gastrointestinal Fate of Scallops and Plant-Based Scallop Analogs

Abstract: Concerns exist regarding the negative environmental impact and health risks associated with ocean fishing and aquaculture, such as stock depletion, pollution, biodiversity loss, and toxin presence. To address these concerns, plant-based seafood analogs are being developed. Our previous study successfully created plant-based scallop analogs using pea proteins and citrus pectin, resembling real scallops in appearance and texture. This study focuses on comparing the digestive fate of these analogs to real scallop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…Several in vitro digestion studies using simulated gastrointestinal tracts have shown that the digestibility of the proteins in plant-based foods are less than those in animal-based foods, which could have nutritional consequences. For instance, the fraction of protein hydrolyzed by the end of digestion under simulated mouth, stomach, and small intestine conditions has been shown to be lower for plant-based meat, egg, and seafood analogs than for the equivalent animal-based products. In vitro digestion studies have also shown that the type of amino acids and peptides produced and their cellular uptake were different for foods made from plant- and animal-based proteins . Moreover, simulated gastrointestinal studies have shown that there are appreciable differences in the effects of plant- and animal-based meat products on the colonic microbiome …”
Section: Reducing Livestock Consumption: Alternative Protein Sourcesmentioning
confidence: 99%
“…Several in vitro digestion studies using simulated gastrointestinal tracts have shown that the digestibility of the proteins in plant-based foods are less than those in animal-based foods, which could have nutritional consequences. For instance, the fraction of protein hydrolyzed by the end of digestion under simulated mouth, stomach, and small intestine conditions has been shown to be lower for plant-based meat, egg, and seafood analogs than for the equivalent animal-based products. In vitro digestion studies have also shown that the type of amino acids and peptides produced and their cellular uptake were different for foods made from plant- and animal-based proteins . Moreover, simulated gastrointestinal studies have shown that there are appreciable differences in the effects of plant- and animal-based meat products on the colonic microbiome …”
Section: Reducing Livestock Consumption: Alternative Protein Sourcesmentioning
confidence: 99%